The Chilean Regulation of Waste Electrical and Electronic Equipment (Weee): Some of the Challenges and Opportunities to Incorporate Informal E-Waste Recyclers - Baigorrotegui-Baigorrotegui, G (Elsevier, 2019)
On June 1, 2016 in Chile is published Law 20920 “Framework for Waste Management, Extended Producer Responsibility and Promotion of Recycling.” This law incorporates waste electrical and electronic equipment (WEEE) as one of six priority products such legislation regulates. This law marks some peculiarities and developments in Latin America regarding the management of WEEE. Since its enunciation, it establishes the extended producer responsibility (EPR). At the same time, it is an excellent example to show how the principle of inclusivity (PI) is constructed and modulated from a Latin American context. This chapter focuses on learnings, implications, and challenges produced along the encounters and affectations between two frames of principles: EPR and PI through the lens of E-waste management system in Chile. Particularly, it will discuss the implication of inclusion of the informal sector in the WEEE formal management system: their possibilities of real participation, the limits, and challenges of this incorporation. © 2020 Elsevier Inc. All rights reserved.